Health Provider Perspectives of Health Facility Preparedness and Organization in Implementation of Option B+ among Pregnant and Lactating Women in Central Uganda: A Qualitative Study. (5th March 2019) - Mukose, Aggrey David; Bastiaens, Hilde; Buregyeya, Esther; Naigino, Rose; Makumbi, Fredrick; Musinguzi, Joshua; Van geertruyden, Jean-Pierre; Wanyenze, Rhoda K.
Introduction: Uganda adopted Option B+ for prevention of mother-to-child transmission (PMTCT) of HIV in 2012. However, there is limited data on preparedness and organization of Option B+ services. These data are critical in informing PMTCT programs and provision of universal antiretroviral therapy (ART) for all populations. This study explored health providers' experiences of preparedness and organization of Option B+ services in Central Uganda. Methods: Key informant interviews with 54 health providers from 6 health facilities in 3 districts were conducted. Thematic approach was employed to analyze data. Results: Themes identified on preparedness were training of frontline health providers and provision of Option B+ guidelines, supervision and mentorship, and provision of essential medicines and medical health supplies, whereas those concerning organization were HIV counseling and testing, ART initiation, follow-up, and patient support mechanisms. Innovations like use of expert clients, assessing women's readiness to start Option B+, and retaining women in antenatal care clinic depending on the need are important in provision of Option B+. Conclusion: This study provides insights into preparedness and organization of Option B+ services which are important in provision of Option B+ and universal ART for all populations. Research around models of follow-up is recommended.